An Extension of the Composite Commodity Theorem: A Note - Fountain, John; Young, Leslie (Quarterly Journal of Economics, 1980)
John Fountain, Leslie Young; An Extension of the Composite Commodity Theorem: A Note, The Quarterly Journal of Economics, Volume 94, Issue 2, 1 March 1980, Page